Advancements in Omniphobic membranes: Properties, fabrication techniques, and applications in membrane distillation - Monis Bin Abid (Desalination and Water Treatment)
Omniphobic membranes signify a significant progression in membrane technology, providing remarkable resistance to wetting and fouling—two critical challenges encountered in membrane distillation (MD) systems. This review offers a thorough yet succinct overview of the fundamental principles, fabrication methodologies, and surface modification techniques employed in developing omniphobic membranes. Particular attention is directed towards recent advancements in phase inversion, electrospinning, and chemical vapor deposition, among other methodologies. The review also assesses various omniphobic membranes' efficacy in treating high-salinity and surfactant-laden wastewater streams. By scrutinizing essential properties such as contact angle, liquid entry pressure (LEP), flux, and long-term stability, this article is a pragmatic resource for researchers striving to engineer high-performance membranes for MD. Prospective research avenues are suggested to enhance membrane durability and scalability for industrial applications.